Generation Z Political Engagement in Tanzania (2022–2025): Consequences for Political Polarization and Social Cohesion - Ruhangisa, Valentine Flavian (Journal Politique, 2026)
Abstract This qualitative study examines the emergence and consolidation of Generation Z (Gen Z) political engagement in Tanzania between 2022 and 2025, with particular attention to its implications for political polarization and social cohesion. As Tanzania’s youngest politically active generation, Gen Z has increasingly relied on digital platforms, informal networks, and issue-based activism to participate in political discourse and civic life. Drawing on qualitative document analysis, discourse analysis of social media content, policy statements, media reports, and relevant scholarly literature, the article explores the forms, dominant narratives, and broader societal implications of Gen Z political engagement. The study argues that Gen Z politics in Tanzania represents a significant transformation in patterns of political participation, characterized by digitally mediated activism, generational identity framing, and strong demands for accountability directed at political elites. While these developments have expanded political voice, civic awareness, and inclusion among young people, they have simultaneously intensified political polarization, heightened generational tensions, and contributed to the fragmentation of public discourse. The findings reveal a central paradox: Gen Z political engagement enhances democratic participation while at the same time posing challenges to social cohesion and deliberative politics. By situating the Tanzanian case within broader debates on youth politics and digital democracy in Africa, the article contributes both empirically and theoretically to scholarship on political socialization, digital public spheres, and social cohesion. The study concludes by emphasizing the importance of inclusive institutional channels, digital civic education, and dialogue-oriented governance strategies to harness the democratic potential of Generation Z while mitigating its polarizing effects